REHABILITASI MEDIK PADA SINDROM MARFAN - Kusmarwaty, Drahma; Mogi, Theresia I. (JURNAL BIOMEDIK : JBM, 2014)
Abstract: Marfan Syndrome (MS) is an autosomal dominant condition of the connective tissue that involves the ocular, cardiovascular and musculoskeletal systems. MS is caused by mutations in the fibrillin-1 gene, leading to joint ligaments flaccidity, joint hypermobility and overgrowth of the long bones. The diagnosis of MS is confirmed by using the Ghent nosology,through a comprehensive assessment largely based on a combination of major and minor clinical manifestations in various organ systems and the family history. The management of MS done with collaboration of team genetic clinic, cardiovascular, orthopedic, eye, and rehabilitation. The aims of rehabilitation of MS patients are to increase pulmonary function, improve exercise endurance, increases bone density, physical strength, prevent scoliosis, education about functional training on activity daily living.Keywords: Marfan syndrome, management, team rehabilitationAbstrak: Sindrom Marfan (SM) adalah autosom dominan dari jaringan ikat yang melibatkan ocular, kardiovaskular dan sistem musculoskeletal. Penyebab SM adalah mutasi dari gen fibrillin-1, yang menyebabkan flaccid ligamen sendi, hipermobilitas sendi dan overgrowth dari tulang panjang. Diagnosis dari SM dengan Ghent nosology, melalui penilaian secara menyeluruh berdasarkan kombinasi dari manifestasi klinik mayor dan minor pada sistem organ dan riwayat keluarga. Penanganan SM dilakukan dengan kolaborasi tim antara lain klinik genetik, kardiovaskular, orthopedi, mata, dan tim rehabilitasi. Tujuan dari rehabilitasi pada SM adalah meningkatkan fungsi paru, meningkatkan ketahanan latihan, meningkatkan densitas tulang, ketahanan fisik, mencegah skoliosis, edukasi mengenai functional training pada aktivitas kehidupan sehari-hari.Kata kunci: sindrom Marfan, penanganan, tim rehabilitasi